Light-driven plasmonic microrobot for nanoparticle manipulation - Jin Qin; Xiaofei Wu; Anke Krueger; Bert Hecht (Nature Communications)
Abstract Recently light-driven microdrones have been demonstrated, making use of plasmonic nanomotors based on directional resonant chiral light scattering. These nanomotors can be addressed individually, without requiring the tracking of a focused laser, leading to exceptional 2D maneuverability which renders microdrones a versatile robotic platform in aqueous environments. Here, we incorporate a light-operated manipulator, a plasmonic nano-tweezer, into the microdrone platform, rendering it a microrobot by enabling precise, all-optical transport and delivery of single nanoparticles suspended in solution. The plasmonic nano-tweezer consists of a resonant cross-antenna nanostructure exhibiting a central near-field hot spot, extending the ability of traditional optical tweezers based on focused laser beams to the trapping of nanoparticles. However, most of plasmonic nano-tweezers are fixed to the substrates and lack mobility. Our plasmonic microrobot utilizes circularly polarized light to control both motors and for stable trapping of a 70-nanometer fluorescent nanodiamond in the cross-antenna center. Complex sequences of microrobot operations, including trap-transport-release-trap-transport actions, demonstrate the microrobot’s versatility and precision in picking up and releasing nanoparticles. Our microrobot design opens potential avenues in advancing nanotechnology and life sciences, with applications in targeted drug delivery, single-cell manipulation, and by providing an advanced quantum sensing platform, facilitating interdisciplinary research at the nanoscale.